2004
DOI: 10.1155/2005/868179
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Management of Asymptomatic Catheter‐Associated Bacteriuria and Candiduria at The Ottawa Hospital

Abstract: Antimicrobial agents were prescribed in over one-half of CAUTI cases, contrary to recommendations from the literature. Education is required to bring this strongly supported recommendation into clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
40
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 16 publications
(28 reference statements)
6
40
1
Order By: Relevance
“…[5][6][7] The findings of these studies as well as our own findings and those of Kelley et al 1 demonstrate a 32%-65% treatment rate of ASB when ASP and ASB education are lacking, despite IDSA guideline recommendations. 1,2,[5][6][7] ASPs are critically important in combating the overuse and misuse of antibiotics. We commend Kelley et al 1 for the success of their ASP educational initiative at decreasing empirical antibiotic prescribing in ASB at their institution.…”
Section: Antibiotic Burden Associated With Treatment Of Asymptomatic supporting
confidence: 66%
See 1 more Smart Citation
“…[5][6][7] The findings of these studies as well as our own findings and those of Kelley et al 1 demonstrate a 32%-65% treatment rate of ASB when ASP and ASB education are lacking, despite IDSA guideline recommendations. 1,2,[5][6][7] ASPs are critically important in combating the overuse and misuse of antibiotics. We commend Kelley et al 1 for the success of their ASP educational initiative at decreasing empirical antibiotic prescribing in ASB at their institution.…”
Section: Antibiotic Burden Associated With Treatment Of Asymptomatic supporting
confidence: 66%
“…And what is considered diarrhea? 6 These ambiguities suggest that the symptom severity threshold for initiating testing could vary significantly between institutions and wards. In addition, use of more…”
mentioning
confidence: 99%
“…Finally, of patients with ASB who had urinary catheters, 55% (26/47 patients) were managed with catheter removal or exchange, which might have directly prevented secondary infections (24). The rates of microbiological eradication were higher among patients with catheter removal or exchange than among those with retained devices (65% versus 50%; P ϭ 0.26).…”
Section: Discussionmentioning
confidence: 99%
“…Old age, long stayin hospital, using broad spectrum antibiotics, and renal defects are the most important predisposing factors for candiduria (1,5,7,8). Several reports have indicated that candiduria is a very common infection in hospitalized patients and its incidence is linked to antibiotic usage, long stay in hospitals, old age etc (2,6,9).…”
Section: Introductionmentioning
confidence: 99%